PENGARUH PROFITABILITAS, LEVERAGE, STRUKTUR KEPEMILIKAN DAN STATUS PERUSAHAAN TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Purwandari, Arum; Purwanto, Agus (Diponegoro Journal of Accounting, 2012)
The purpose of this study was to analyze the influence between profitability ratio, leverage ratio, public ownership, institutional ownership, managerial ownership, the corporate status and the disclosure of the financial statements in manufacturing companies. The population on this research were 148 manufacturing companies in Indonesia Stock Exchange within period 2009-2010. The sample size was determined by purposive sampling method which based on certain criteria, consisted of 98 companies for 2-years study (2009-2010). So the collected data were (n) = 2 x 98 = 196. The results showed that there were no significant influence between profitability, leverage, corporate status and the index Wallace partially. Other findings showed that there ware a significant influence between the public ownership, institutional ownership, managerial ownership and the index Wallace partially.